Newsletter Publishing with Pagemaker / Macintosh Edition - Barry John A.; Davis Frederic E; Hall Martin L. W (Don Jones-Irwin, 1987)
Desktop Newsletter Publishing, PageMaker Examined, The Macintosh in Desktop Publishing, The Process of Desktop Publishing, Glossary, Index.